Influence Of Probiotics Em-4 (Effective Microorganism-4) At Different Doses On The Sustenance And Growth Of Large Payau Nila Fish (Oreochromis Niloticus) - Manullang, Helentina Mariance; Lubis, Muya Syaroh Iwanda; Hasan, Uswatul (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2025)
The Effect of Adding Natural Ingredients to Artificial Feed on the Color Brightness Level of Goldfish (Cyprinus carpio Linn). This research aims to determine the effect of adding natural ingredients to artificial feed on the level of color brightness of goldfish (Cyprinus carpio Linn), and the growth rate and survival rate of the test fish. The method used in this research is an experimental method using a Completely Randomized Design (CRD) consisting of 4 treatments and 3 replications with a feeding frequency of three times per day with a percentage of 5% of the body weight of the test fish, a natural ingredient used in making artificial feed. These are pumpkin flour (Cucurbita moschata), mangosteen rind flour (Garcinia mangostana L), and carrot flour (Daucus carota L) with the same dose in each treatment, namely 25% of 1 kg of feed. Based on the results of variance analysis, the brightness level of goldfish color has a very real influence. The highest increase in the color of the test fish was obtained in treatment A, pumpkin flour, amounting to (1.37) on the Toca color finder scale (from pale orange to dark orange), followed by the second highest in treatment C, carrot flour, amounting to (1.2), treatment B flour. Mangosteen peel was in third position with an increase in color of (0.94) and the lowest increase in color change occurred in treatment D (control = without the addition of natural ingredients) of 0.7. However, absolute weight and length growth did not have a real influence. The overall graduation rate is 87.49%. The average water quality parameters are temperature 26-29oC, pH 7.5-7.9 and ammonia 0.25 ppm.